Teachers from Community Tele-Baccalaureates, profiles that guide the practice and flexibility of the teaching processes - Estrada Ruiz, Marcos Jacobo; Alejo López, Sergio Jacinto (IE Revista de Investigación Educativa de la REDIECH, 2021)
This article presents results of a research that aimed to analyze the profile and work conditions for teachers that belong to the Community Tele-Baccalaureates (TBC) in Guanajuato, Mexico. Specially, in this paper we focused on answering questions related to teachers’ profile and their relationship with the type of teaching taken on, and how their profile and incorporation process determine the results. The CIPP (Context, Input, Process, Product) model was followed for the development of the measurement tools and a qualitative approach was assumed from which interpretive strategies were prioritized. Information obtained through in-depth interviews conducted with CTB teachers from two municipalities in the state of Guanajuato are presented. Among other results, these institutions are characterized as an educational option marked by precariousness. Also, it shows how the profile of teachers guides their practice and the type of work they do in the classroom, impacting the learning processes of students and having the flexibility of such processes as a characteristic.